Assessments of gully erosion susceptibility in typical thick-layer Mollisol region of Northeast China - Binglong Wu; Fenli Zheng; Ximeng Xu; Yucheng Fu; Dennis C. Flanagan; Rong Li; Jiaqiong Zhang; Bin Wang; Jinxia Fu (Soil and Tillage Research, 2026)

Soil degradation impacts on root water uptake and yield of soybean in the black soil region - Zhijie Li; Zhuohang Jin; Ying Song; Jinxia Fu; Xiaoling He; Fenli Zheng; Wenxiu Zou; Zhi Li (Soil and Tillage Research, 2026)

Integrated implementation of conservation agriculture enhances crop yield and sustains multiple ecosystem services in the black soil regions - Ying Song; Zhijie Li; Jiahui Ha; Xiaoling He; Jinxia Fu; Fenli Zheng; Zhi Li (Agriculture, Ecosystems & Environment, 2026)

Optimized straw–nitrogen management enhances crop yield, soil carbon sequestration, and economic returns in dryland maize systems of Northwest China - Yunfei Ren; Jiayi Li; Fu Liu; Longchuang Zhang; Xiu Chen; Haibo Hu; Xiaoyu Ning; Yeye Zhang; Jinxia Wang; Xiaozhou Li; Shuangguo Zhu; Fei Mo (Soil and Tillage Research, 2026)

Design of High-Energy-Density fuels based on COSMO-RS - Jinxia Fu; Scott Q. Turn (Fuel, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Microbial insights into a high water-quality dependent freshwater snail: Geographical origin and rearing mode shape the gut antibiotic resistance gene profile of Sulcospira hainanensis - Lingtong Ye; Chen Chen; Shengli Fu; Jie Lu; Tuo Yao; Huajian Lin; Zhifu Liang; Huan Li; Jinxia Peng; Zhenhua Ma (Environmental Pollution, 2026)

Contrasting but complementary: divergent impacts of no-till and deep tillage on soil health in black soil regions globally - Ying Song; Zhijie Li; Jinxia Fu; Fenli Zheng; Yakov Kuzyakov; Zhi Li (Journal of Cleaner Production, 2026)

Water-saving Effect of Domestic and Industrial Water Pricing Policies Using Nonlinear Fixed-effect Models - Hongwei Cai; Yan Bo; Jin Fu; Jiadi Zou; Zhijian Yu; Wulahati Adalibieke; Jinxia Wang; Yazhen Gong; Feng Zhou (Chinese Geographical Science, 2026)

38 years of micronutrient fertilization, particularly copper, enhance winter wheat yield during drought on the Loess Plateau without yield penalties - Xiaozhou Li; Fu Liu; Yunfei Ren; Jinxia Wang; Haibo Hu; Shuangguo Zhu; Fei Mo (Field Crops Research, 2026)

Crop yield–soil quality trade-offs under no-tillage and deep tillage in the black soil region of Northeast China - Ying Song; Xiaoling He; Jinxia Fu; Fenli Zheng; Zhi Li (Field Crops Research, 2026)

Unraveling the regional dynamics of straw mulching and incorporation on crop yields in Northeast China - Ying Song; Zhijie Li; Xiaoling He; Jiaqiong Zhang; Jinxia Fu; Fenli Zheng; Zhi Li (European Journal of Agronomy, 2026)

Responses of crop yield and soil quality to organic material application in the black soil region of Northeast China - Ying Song; Zhijie Li; Hanwen Chen; Jiayu Sun; Xiaoling He; Jinxia Fu; Fenli Zheng; Zhi Li (Soil and Tillage Research, 2025)

Soil thinning dominates crop yield reduction among various degradation types in the typical black soil region of Northeast China - Ying Song; Zhijie Li; Jiayu Sun; Hanwen Chen; Jinxia Fu; Xiaoling He; Asim Biswas; Fenli Zheng; Zhi Li (European Journal of Agronomy, 2025)

Local and downwind precipitation has been boosted by evapotranspiration change-induced moisture recycling in the Chinese Loess Plateau - Chao Gao; Jinxia Fu; Zhiming Han; Wangjia Ji; Liu Zhao; Xiaohua Wei; Zhi Li (Agricultural and Forest Meteorology, 2025)

Oxidation mechanism of sulfur-containing compounds and antioxidant depletion dynamics: Insights into interactions - Jinxia Fu; Scott Q. Turn (Fuel, 2025)

Dynamic assessment of the impact of compound dry-hot conditions on global terrestrial water storage - Zhiming Han; Hongbo Zhang; Jinxia Fu; Zhengshi Wang; Limin Duan; Wenrui Zhang; Zhi Li (Remote Sensing of Environment, 2024)

The development of novel genome-SSRs, multiplex PCR panels, and allelic ladders for parentage identification in Tachypleus tridentatus - Boyu Chen; Ju Long; Jinxia Liu; Pengliang Wang; Zihang Ma; Zhenyu Lan; Ziwei Liang; Qianni Fu; Zining Zhang; Yan Zhang; Yitao Duan; Peng Zhu; et al. (Aquaculture, 2024)

Unraveling hierarchical hollow NiCo2S4/MXene/N-doped carbon microspheres via dual templates for high-performance hybrid supercapacitors - Baobao Li; Lu Zhang; Zhibo Zhao; Yuxi Zou; Bingqi Chen; Xiaoguang Fu; Fangqiao Wang; Sishi Long; Wenxi Guo; Jinxia Liang; Meidan Ye (Chemical Engineering Journal, 2024)

Sustainable production 3-bromobutyrates and 3-hydroxybutyrates from bioderived poly-3-hydroxybutyrate - Shimin Kang; Peifeng Tang; Jianhao Liang; Jinxia Fu; Jintao Chen; Xiting Zheng; Juntao Wang; Jun Ye; Yongjun Xu (Sustainable Chemistry and Pharmacy, 2023)

Sustainable production of drop-in butyric acid from bioderived poly(3-hydroxybutyrate) - Shimin Kang; Jianhao Liang; Jinxia Fu; Jiaqi Feng; Zaiming Tan; Zizhi Huang; Hang Zhang; Yongjun Xu (Sustainable Chemistry and Pharmacy, 2023)

Rainfall partitioning and its influence on dissolved carbon and nitrogen fluxes through plant-soil system of a xerophytic shrub in northern China - Jinxia An; Guangyao Gao; Juan Pinos; David Dunkerley; Yiming Shao; Bojie Fu (Journal of Hydrology, 2023)

Corrigendum to “Near-zero-waste hydrogenolysis of poly(lactic acid) to biofuel” [Fuel 334 (2022) 126609] - Jialin Xu; Kuo Zhou; Jinxia Fu; Zaiming Tan; Linlin Qin; Peigao Duan; Yongjun Xu; Shimin Kang (Fuel, 2023)

Daily precipitation and temperature for 2021–2050 over China: Multiple RCMs and emission scenarios corrected by a trend‐preserving method - Jingpeng Zhang; Shouzhang Peng; Zhengshi Wang; Jinxia Fu; Zhi Li (International Journal of Climatology, 2023)
Daily climate data are extremely important to drive ecological models, but the outputs of climate models are often deviated from the observations. The bias correction methods mostly highlight the target statistical parameters (e.g., mean and variance) for a target period, but perturb the simulated change trend and variability. In this study, we utilize a trend‐preserving bias correction method that can simultaneously consider the frequency and intensity of climatic variables to adjust the daily maximum and minimum temperature, and precipitation (Tmax, Tmin, and Pre) from CORDEX‐EA regional climate models for the period of 2021–2050 over China. Results show that: (a) the bias correction method greatly improves the spatial patterns of simulated Tmax, Tmin, and Pre since the corrected data has higher correlation and smaller differences across the whole domain. The differences in mean Tmax, Tmin, and Pre between climate models and observations have been reduced from −4.5 ± 6.41°C, −2.06 ± 0.58°C, 177.25 ± 51.55 mm before correction to 0.01 ± 0.02°C, −0.01 ± 0.02°C, −26.22 ± 6.39 mm after correction, respectively. In addition, the simulated change trend and climate variability at all time scales are well preserved. (b) Spatially, the warming rates in the west would be higher than in the east, and they are larger under the most severe future emissions scenario (RCP8.5) relative to the low‐mid emissions scenario (RCP4.5). The Pre change would mainly occur over east China with the significant upward trend. The dataset presented in this article has been published in the Network Common Data Form (NetCDF) File Format at https://doi.org/10.5281/zenodo.5058620 .

Growth of winter wheat adapting to climate warming may face more low‐temperature damage - Yanling Song; Guangsheng Zhou; Hans W. Linderholm; Junfang Wang; Yong Li; Guofu Wang; Yan Fu; Jinxia Xu; Ying Shi; Ying Xu; Hui Gao; Deliang Chen (International Journal of Climatology, 2023)
China's surface air temperature is increasing due to global warming, so it is interesting that how low temperatures would be changed during the growth period of winter wheat in future. We focused on the low temperatures of winter wheat from 2021 to 2050, using temperatures under the high emission scenario Representative Concentration Pathway 8.5 (RCP8.5) projected by the RegCM4.4 regional climate model. The results showed that the annual mean temperature was projected to increase by 0.42°C⋅decade −1 in the northern and by 0.35°C⋅decade −1 in the southern winter wheat region. Furthermore, the temperature was expected to increase rapidly in spring, which could advance the dates of flowering and the start of the grain‐filling period. Using the genetic parameters determined by the calibration and validation of WOFOST and bias‐corrected projected meteorological data, simulations of winter wheat growth were performed over the winter wheat region for 2021–2050. The simulated number of days to the flowering period of winter wheat for 2041–2050 was on average 6.5 days less than in 2021–2030, due to the spring warming. Because of the earlier start of the growing season, winter wheat could face negative effects by being subjected to low temperatures. Indeed, the number of low‐temperature days was projected to increase by 110% from 2041 to 2050 compared to 2021–2030, and the number of killing degree days (KDDs) is projected to increase by 120% at the same time. If the number of days to flowering did not change, the number of low‐temperature days and KDDs only changed slightly, showing that the negative influence of low temperature was mainly caused by the advancement of the flowering date. The effect of low temperature on growth was underestimated when the response of winter wheat growth to global warming was not considered.

Near-zero-waste hydrogenolysis of poly(lactic acid) to biofuel - Jialin Xu; Kuo Zhou; Jinxia Fu; Zaiming Tan; Linlin Qin; Peigao Duan; Yongjun Xu; Shimin Kang (Fuel, 2023)

Dissolved water in jet fuels: a low-temperature quality and water solubility study - Jinxia Fu (Fuel, 2023)

Projecting extreme climate events in China’s Loess Plateau: multiple RCMs and emission scenarios corrected by a trend-preserving method - Yuling Ren; Jingpeng Zhang; Bingbing Li; Jinxia Fu; Zhi Li (Theoretical and Applied Climatology, 2023)

Cloning of Two HSP Genes of Eriocheir hepuensis and Their Expression under Vibrio parahaemolyticus Stress - Qianni Fu; Jinxia Liu; Tianjiao Ren; Zining Zhang; Zihang Ma; Zhenyu Lan; Yitao Duan; Ziwei Liang; Boyu Chen; Yan Zhang; Peng Zhu; Yongyan Liao (Fishes, 2022)
Heat shock proteins (HSPs) are molecular chaperone proteins that can help maintain cellular protein homeostasis, assist in correcting the folding of cellular proteins, and protect organisms from stress when the body is under stress conditions such as temperature changes or bacterial infections. In this study, the HSP10 and HSP40 genes of Eriocheir hepuensis were cloned and named Eh-HSP10 and Eh-HSP40. The results show that the coding sequence length of the HSP10 and HSP40 genes of E. hepuensis was 309 bp and 1191 bp, encoding 102 and 396 amino acids, respectively. The results of protein domain prediction show that Eh-HSP10 has a Cpn10 domain. The Eh-HSP40 protein contains a DnaJ domain, which is characteristic of the HSP40 gene family. The results of qRT-PCR show that the Eh-HSP10 and Eh-HSP40 genes were expressed in different normal tissues, with the highest expression in the heart. Under Vibrio parahaemolyticus stress, the Eh-HSP10 genes peaked at 6 h, and the Eh-HSP40 peaked at 9 h in the hepatopancreas. In the gill, Eh-HSP10 showed a double peak at 24 and 48 h, and the expression of Eh-HSP40 was time-dependent. In the heart, the expression of Eh-HSP10 increased first and then decreased, whereas Eh-HSP40 peaked at 48 h. The results indicate that the Eh-HSP10 and Eh-HSP40 proteins may play a role in protecting E. hepuensis under V. parahaemolyticus infection and that they may be involved in the innate immune response of E. hepuensis against bacteria.

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Estrogen deficiency compromised the β2AR-Gs/Gi coupling: implications for arrhythmia and cardiac injury - Hongjian Hou; Zhiwei Zhao; Jeremiah Ong’achwa Machuki; Lin Zhang; Yan Zhang; Lu Fu; Jinxia Wu; Yuyu Liu; Sian E. Harding; Hong Sun (Pflügers Archiv - European Journal of Physiology, 2018)

Selenium Promotes the Growth and Photosynthesis of Tomato Seedlings Under Salt Stress by Enhancing Chloroplast Antioxidant Defense System - Ming Diao; Long Ma; Jianwei Wang; Jinxia Cui; Aifei Fu; Hui-ying Liu (Journal of Plant Growth Regulation, 2014)

Sedimentary filling and sequence structure dominated by T-R cycles of the Nenjiang Formation in the Songliao Basin - ChenChen Zhang; Shun Zhang; Wei Wei; ChaoDong Wu; JiangPing Liang; Wen Niu; JinXia Du; XiuLi Fu; KunNing Cui; Chao Wang; Hui Wang (Science China Earth Sciences, 2014)